Recent advances in studies of soil organic carbon stability in Karst areas - He, Jie; Liu, Xi; Meng, Wenping; Chen, Xue (Frontiers in Forests and Global Change, 2024)
The stability of soil organic carbon (SOC) is crucial for the global carbon cycle and serves as a key indicator of soil quality and eco-system function. In Karst areas, SOC stability is influenced by unique geological conditions. Studying SOC stability in these regions is significant for understanding regional ecosystem functions and the role of SOC in mitigating global climate change. This review examines the fractions and stability of SOC in Karst areas, analyzing the impacts of key factors such as rocky desertification, land use changes, and vegetation restoration on SOC stability, along with their underlying mechanisms. It also discusses the current challenges and opportunities in SOC stability. This review aims to guide the development of effective ecological rehabilitation and management strategies for degraded ecosystems in Karst areas.